THE FACTORS CAUSING STUDENT’S RELUCTANCE IN ENGLISH ORAL PERFORMANCE IN CLASSROOM ACTIVITIES - Hafsah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose of this research is to investigate student’s reluctance in performing English orally in classroom activities. The research was designed as a case study. To collect data, the research involved a student who was currently studying in the sixth semester. The student was enrolled at the English education study program of Tanjungpura University in academic year 2016/2017. In this research, the participant was observed for 10 times completed with an observation checklist and a field-note for each observation. After that, the researcher gave her questionnaires and an interview guide.The finding showed that the participant was reluctant to use English in the classroom activities because she seemed to have no motivation to speak in English because she was shy and did not get motivation from her classmates to speak in English. She also had no motivation to make an effort in expressing her ideas in English.She was also shy and afraid of making mistakes because she was worried if she used incorrect grammar. Then, she was also confused which tenses to use when speaking. Finally, it was reported that she did not have adequate numbers of words to express her ideas, because she was panic when speaking in English. Keywords: Causes, Reluctance, Oral Performance